Demonstration of RSFQ digitizer on a multichip module. - Joonhee Kang (IEEE Transactions on applied superconductivity)
A 1-b slice of a rapid single-flux quantum (RSFQ) digitizer with interchip communications on a multichip module (MCM) has been successfully designed, fabricated using 3-μm Nb technology, and tested. We placed a flash comparator followed by an enable switch and an MCM transmitter circuit on one side of the chip, and an MCM receiver circuit followed by a memory buffer on the other side. The 5 × 5 mm chip was flip-chip mounted on a 10 × 10 mm carrier chip by a solder bump technique. During circuit operation, the comparator output signal and the clock signal left the chip, moved to the carrier chip, and returned back to the chip into the memory buffer. We operated the circuit with a beat frequency technique where the data input frequency was slightly off from the clock frequency by the beat frequency of 10 kHz. The circuit operated correctly up to 10 GHz. The critical circuit operation margin was observed to be the bias current to the SQUID in the MCM receiver circuit and was about ±6% at 10 GHz